Clinical guide to the treatment of the mentally ill homeless person - Gillig, Paulette Marie (American Psychiatric Publ., 2006)
Mental illness homelessness and clinical practice: an introduction / Hunter L. McQuistion and Paulette Marie Gillig -- General concepts of outreach and engagement / Neil Falk -- Adult shelters / Elizabeth Oudens and Hunter L. McQuistion -- Family shelters / Alan Felix and Judith Samuels -- Assertive community treatment (ACT) teams / Ann Hackman and Lisa Dixon -- Supportive housing / Ralph Aquila, John Kelleher and Thomas Sweet -- Mobile crisis teams / Anthony T. Ng -- Psychiatric emergency services / Avrim Fishkind and Scott Zeller -- Psychiatric inpatient settings / David Nardacci -- Primary care settings / Brian D. Bronson and Anne M. Piette -- Homeless children / Manoj Shah and Randie Schachter -- Jails and prisons / Eric Roskes and Fred Osher -- Homeless veterans / Florence Coleman, Julie Gentile and Ann Morrison -- Homeless, mentally ill persons in rural settings / Jennifer Dempster and Paulette Marie Gillig